Δ‐Myrtoxin‐Mp1a is a Helical Heterodimer from the Venom of the Jack Jumper Ant that has Antimicrobial, Membrane‐Disrupting, and Nociceptive Activities. Issue 29 (13th June 2017) - Dekan, Zoltan; Headey, Stephen J.; Scanlon, Martin; Baldo, Brian A.; Lee, Tzong‐Hsien; Aguilar, Marie‐Isabel; Deuis, Jennifer R.; Vetter, Irina; Elliott, Alysha G.; Amado, Maite; Cooper, Matthew A.; Alewood, Dianne; et al.
Abstract: Δ‐Myrtoxin‐Mp1a (Mp1a), a 49‐residue heterodimeric peptide from the venom of Myrmecia pilosula, comprises a 26‐mer A chain and a 23‐mer B chain connected by two disulfide bonds in an antiparallel arrangement. Combination of the individual synthetic chains through aerial oxidation remarkably resulted in the self‐assembly of Mp1a as a homogenous product without the need for directed disulfide‐bond formation. NMR analysis revealed a well‐defined, unique structure containing an antiparallel α‐helix pair. Dual polarization interferometry (DPI) analysis showed strong interaction with supported lipid bilayers and insertion within the bilayers. Mp1a caused non‐specific Ca 2+ influx in SH‐SY5Y cells with a half maximal effective concentration (EC50 ) of 4.3 μm . Mp1a also displayed broad‐spectrum antimicrobial activity, with the highest potency against Gram‐negative Acinetobacter baumannii (MIC 25 nm ). Intraplantar injection (10 μm ) in mice elicited spontaneous pain and mechanical allodynia. Single‐ and two‐chain mimetics of Mp1a revealed functional selectivity. Abstract : Two of a kind : Mp1a is a structurally unique heterodimeric peptide consisting of paired α‐helical chains connected by two disulfide bonds in an antiparallel arrangement. Synthesis was realized through self‐directed dimerization into the native structure. Mp1a possesses strong membrane‐binding and membrane‐disrupting properties, as well as broad‐spectrum antimicrobial and in vivo nociceptive properties.